Dari Ruang Privat ke Ruang Publik: Analisis Etika Komunikasi dan Peran Media Massa dalam Kasus Pelecehan Verbal di Grup WhatsApp - Badrul Helmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study analyzes the transformation of communication from private to public spaces in a verbal harassment case within a WhatsApp group, and examines the role of mass media in framing the case. Using a descriptive qualitative method with a media-based case study approach, data were collected from online news, media articles, and digital documentation. Analysis was conducted through content analysis and simple framing techniques. The findings reveal that private communication can easily shift into public consumption through screenshots and social media virality. Ethical violations were identified in the form of verbal harassment disguised as humor, reflecting decreased ethical sensitivity in digital spaces. Mass media play a strategic role as information amplifiers and social reality constructors through framing processes that rapidly and deterministically shape public opinion. This study highlights the urgency of ethical awareness, communication responsibility, and digital literacy in navigating the dynamics of the post-privacy era.